O estado da arte sobre processo administrativo e seu enfoque disciplinar - Figueiredo, Tertuliano Rosenthal (2019)
The present study focused on the administrative process theme emphasizing the mapping of the field of study of this institute that has been considered a tool to control administrative acts sensitive to the wishes of the Public Administrators and Society, as well as being a way for the building of greater credibility for legal-political institutions. Taking this theme for granted, this research aimed to develop a mapping of the field of study on administrative process focusing on the specific administrative disciplinary process. According to the methodological construction adopted, this research is classified by its exploratory, descriptive and explanatory nature due its ends as well as by its quali-quantitative nature due its means, both developed through a deductive/ theoretical-legal method that is oriented to apprehend the field of study and the state of the art on administrative process with focus on the specific administrative disciplinary process. On one hand, the methodological procedures of data collection have been performed through a systemic analysis that combined integrative, bibliographical and legal review. On the other hand, the procedures of data analysis have been perfomed by the instruments of graphic analysis and legal hermeneutics. It is concluded from the results presented in this dissertation that the Administrative Disciplinary Process has been understood legally as a generalist phenomenon from the Public Administration eminently backed by the Constitution and by a recognized restricted majority doctrine widely consolidated in the legal environment in comparison to the Administrative Disciplinary Process which in its specificity lacks not only a deepening of doctrine but also an amplified repercussion.